Research status of selective laser melting aluminum alloys - WU Ling-zhi; WEN Yao-jie; ZHANG Bai-cheng; YIN Hai-qing; QU Xuan-hui (Fenmo yejin jishu)
Selective laser melting (SLM) technology has been widely applied in the industry due to its customization, short manufacturing cycle, and high precision. The research progress of aluminum alloys and composites prepared by SLM was systematically reviewed. The advantage of SLM aluminum alloys was introduced though the SLM characterization. The research of SLM casting Al‒Si series alloys was discussed, and the microstructure, phase composition, and mechanical properties was revolved, combining with the scanning strategy and laser parameter optimization. Meanwhile, the investigation of SLM nano/micro reinforced aluminum alloys was also present, the particle reinforcement mechanism on the microstructure, relative density, wettability, and mechanical properties was analyzed. On the other hand, the research progress of new high strength aluminum alloys prepared by SLM was also discussed, the strengthening mechanism, relative density, and mechanical properties were emphasized. Finally, the development trend of SLM aluminum alloys and the current problems were prospected.